Translational neuronal ensembles: Neuronal microcircuits in psychology, physiology, pharmacology and pathology - Lara-González, Esther; Padilla-Orozco, Montserrat; Fuentes-Serrano, Alejandra; Bargas, José; Duhne, Mariana (Frontiers in Systems Neuroscience, 2022)
Multi-recording shows that neurons coordinate their firing to work together forming ensembles. Neuronal circuits are made by connections between ensembles. While “canonical” microcircuits are composed of interconnected principal neurons and interneurons, it is not clear how they comprise a neuronal ensemble. Synaptic connections and plasticity between neurons are complex. To fill the gap between cellular-synaptic and circuits levels two assumptions are made: First, whatever the nature of the connections these may be simplified by “functional connections”. Second, whatever the mechanisms to achieve potentiation or depression, synaptic weights of the circuits and the resultant flow of activity are relatively stable. These assumptions have experimental basis cited in this review. Tools to analyze ensembles in terms of neuronal populations are being developed. Circuits processing can be followed with multi-recording techniques as temporal sequences of alternating neuronal ensembles resembling computational routines. Temporal sequences can be aligned with the steps of behavioral tasks, supporting the hypothesis that consider them memory traces, which can be manipulated to modify behavior. Alternative trajectories make circuits flexible and adaptive. In vitro recordings have shown that temporal sequences can be contained in a piece of isolated tissue of histological scale. Moreover, it has been shown that sequences found in control conditions differ from those recorded in pathological tissue obtained from animal disease models. The actions of clinically used drugs to treat disease states are clearly discernible, setting the basis for bio-assays to test drugs with potential clinical use. The neuronal ensembles theoretical framework has become a dynamic neuroscience paradigm.